1999
DOI: 10.1016/s0038-1098(99)00347-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for fast cluster formation of chain oxygen vacancies in YBa2Cu3O7−δ as the origin of the fishtail anomaly

Abstract: We report on three different and complementary measurements, namely magnetisation measurements positron annihilation spectroscopy and NMR measurements, which give evidence that the formation of oxygen vacancy clusters is on the origin of the fishtail anomaly in YBa 2 Cu 3 O 7−δ . While in the case of YBa 2 Cu 3 O 7.0 the anomaly is intrinsically absent, it can be suppressed in the optimally doped state where vacancies are present. We therefore conclude that the single vacancies or point defects can not be resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Hence, there is a certain range of magnetic fields, 20Oe-100Oe at T=70K and 0-200Oe at T=50K, in which J C increases with increasing applied field before it starts to decrease above the fields H P70 and H p50 at which the J C peaks appear. Similar results have been obtained by altering the local distributions of the oxygen in the YBCO structure [7,8], where the authors concluded that the peak effect in YBCO is correlated with clustering of the oxygen vacancies. Like in the hysteresis loops measurements, the J C plots are dominated by two contributions, the background contribution of inter-grain currents -typical of a bulk sample (represented by dashed lines in the figure) -and the intra-grain contribution of field-induced pinning (originating the peak effect) which might be caused by clusters of oxygen vacancies in the Cu-O chains.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Hence, there is a certain range of magnetic fields, 20Oe-100Oe at T=70K and 0-200Oe at T=50K, in which J C increases with increasing applied field before it starts to decrease above the fields H P70 and H p50 at which the J C peaks appear. Similar results have been obtained by altering the local distributions of the oxygen in the YBCO structure [7,8], where the authors concluded that the peak effect in YBCO is correlated with clustering of the oxygen vacancies. Like in the hysteresis loops measurements, the J C plots are dominated by two contributions, the background contribution of inter-grain currents -typical of a bulk sample (represented by dashed lines in the figure) -and the intra-grain contribution of field-induced pinning (originating the peak effect) which might be caused by clusters of oxygen vacancies in the Cu-O chains.…”
Section: Resultssupporting
confidence: 75%
“…Another example is the peak effect which appears on critical current density (J C ) plots of structurally altered HTCSs [4,5]. This can originate from structural defects such as intrinsic pinning of vortices at the CuO 2 planes [6] or from oxygen vacancy clusters [7,8]. Most studies about altered HTCS structures have been focused on YBCO [9].…”
Section: Introductionmentioning
confidence: 99%
“…clusters of oxygen vacancies effectively act as residual impurities, [21] introducing scattering that could modify drastically the shape of the DOS at E = 0 in a d-wave superconductor, [22] and a correlation has been observed between the concentration of oxygen vacancies and the amplitude of the Schottky anomaly, [23] which tends to mask the d-wave contribution.…”
Section: Samplementioning
confidence: 99%
“…Certainly, it is known that a weak domain disorder is necessary to pin vortices, to observe the vortex lattice via STM. 34 Also, the role of the interstitial oxygen in the superlattice modulations in Bi2212 needs to be better understood. The strength of this modulation suggests that it is associated with an ordering of the interstitial oxygen, but this should lead to a strong correlation between the domains and the superlattice, which seems not to be the case.…”
Section: Domain Phasementioning
confidence: 99%